Parameter identification of inelastic structures under dynamic loads. - Zhang, Haochuan
The generalized model of differential hysteresis contain 13 control parameters with which it can curve fit practically any hysteretic trace. Three identification algorithms are developed to estimate the control parameters of hysteresis for different classes of inelastic structures. These algorithms are based upon the simplex, extended Kalman filter, and generalized reduced gradient methods. Novel techniques such as global search and internal constraints are incorporated to facilitate convergence and stability. Effectiveness of the devised algorithms is demonstrated through simulations of two inelastic systems with both pinching and degradation characteristics in their hysteretic traces. Owing to very modest computing requirements, these identification algorithms may become acceptable as a design tool for mapping the hysteretic traces of inelastic structures.
Keywords: System identification; Hysteresis; Simplex; Reduced gradient; Kalman filter